Pengembangan Ekstrakurikuler Siswa Sekolah Dasar SD Negeri 176371 Sigumpar Jae dalam Bidang Olahraga dan Seni melalui Program KPPM - Tri Astina Pangaribuan; Samuel Marolop Pasaribu; Mangihut Jhon David Sinaga; Dame Fernando Pardede; Andreas Sitorus; Winfrontstein Naibaho (Jurnal Pengabdian Masyarakat, 2026)
The Community Service Program (KPPM) is an embodiment of the Tri Dharma of Higher Education, aiming to integrate students' scientific knowledge with the real needs of the community, particularly in the primary education sector in rural areas. This study aims to describe the implementation and impact of developing extracurricular activities in the fields of sports (volleyball and sprinting) and arts (marching band, guitar, pianica, and drawing) at SD Negeri 176371 Sigumpar Jae, Toba Regency. The method employed was direct mentoring and guided practice over a one-week period, involving students from various academic backgrounds. The results of the service showed an increase in student enthusiasm, mastery of basic sports techniques, and the development of artistic creativity and self-confidence. In conclusion, strengthening extracurricular programs through KPPM intervention has proven effective as a catalyst for developing students' non-academic potential and building characters of discipline and sportsmanship, while simultaneously contributing to the reinforcement of the Pancasila Student Profile at the primary education level. This activity is also expected to increase collaboration between universities and the community in creating a more inclusive and sustainable educational environment.